Data base of Measurement of actual energy expenditure when using a commercial device for exercising at home - Montoya Arroyo, Jhonny Alberto (2021)
The evidence on the importance of regular exercise is overwhelming. Awareness of this fact leads many people to resort to simple, attractive solutions marketed through TV. Many countries, unfortunately, lack strict regulations to assess the claims made by commercial items. Moreover, it would seem that requirements for scientific evaluation of exercise-related products do not exist at all. Every time someone purchases exercising equipment and shortly afterwards decides to give up working out because no positive results can be seen, one step backwards is taken in public health. The purpose of this study was to measure the actual energy expenditure induced by using a commercially available device for exercising at home and compare it to the claims made about it in advertising. Various field and laboratory methods were used to measure the energy expenditure of 27 young, apparently healthy students (15F, 12 M; 19.1 ± 1.0 years old; 1.647 ± .073 m; 63.09 ± 10.13 kg; mean ± SD) while they were resting for 10 minutes in supine position, and then while working out on the equipment at medium speed for 10 minutes. None of the methods used showed a gross energy expenditure above 272 kJ (65 kcal) in 10 min activity. Oxygen consumption during stress was equivalent to 1.54 ± .23 MET, corresponding to 23.4 ± 9.2 kJ (5.6 ± 2.2 kcal) net expenditure, or 70.3 ± 11.7 kJ (16.8 ± 2.8 kcal) gross expenditure. In contrast, the gross energy expenditure reported in the equipment’s commercial is 277 kcal (1159 kJ) for 10 min. In conclusion, the actual net energy expenditure is 1/50 (two hundredths) the energy expenditure being claimed in the advertisements.